Polarization multiplexed bit data recording to submicron-particles-arrayed optical storage - Okuzono, Daiki; Egami, Chikara (Oficyna Wydawnicza Politechniki Wrocławskiej, 2022)
In this study, a submicron-particles-arrayed optical storage disk was fabricated by the spin coating method. Moreover, we have formed a multi-valued pit by irradiating linearly polarized laser beams at multiple angles (0° and 90°). The optical setup has the semiconductor laser (λ = 637 nm) for reconstructing and the SHG-YVO4 laser (λ = 532 nm) for recording. The optical setup measured the submicron-particles-arrayed optical storage as a confocal image by 2D scanning with a motorized stage.
Optica Applicata, Vol. 52, 2022, nr 1, s. 67-76
Optica Applicata is an international journal, published in a non-periodical form in the years 1971-1973 and quarterly since 1973. From the beginning of the year 2008, Optica Applicata is an Open Access journal available online via the Internet, with free access to the full text of articles serving the best interests of the scientific community. The journal is abstracted and indexed in: Chemical Abstracts, Compendex, Current Contents, Inspec, Referativnyj Zhurnal, SCI Expanded, Scopus, Ulrich’s Periodicals Directory
http://opticaapplicata.pwr.edu.pl/
Keywords: optyka; submicron-particle; confocal microscope; optical storage